An Investigation on Factors Impacting Satisfaction and Continuance Intention to Use E-Learning Among University Lecturers in Zhejiang, China - Li, Jiahui (Scholar: Human Sciences, 2024)
Purpose: This study aims to investigate factors contribute to the satisfaction and continuance intentions to use e-learning among university lecturers in Zhejiang, China. This conceptual framework was developed based on a review of previous theoretical frameworks of research, proposing a causal relationship among course attributes, system attributes, instructor attributes, interactive attributes, social influence, user satisfaction, and continuance intention. Research design, data, and methodology: The research was conducted quantitative method (n=500), with questionnaires distributed to lecturers in five universities in Zhejiang, China. The sampling procedures involve purposive, stratified random and convenience sampling. An expert rating of the item-objective congruence (IOC) index and a pilot test for 30 respondents were conducted to confirm reliability and validity before the data collection. Structural Equation Modeling and Confirmatory Factor Analysis were used to evaluate construct fit, reliability, and validity. Results: The results explicate that course attributes, system attributes, instructor attributes significantly impact satisfaction. Continuance intention is significantly impacted by social influence and satisfaction. However, interactive attributes have no significant impact on user satisfaction. Conclusions: Educational institutions, universities, and lecturers are suggested to provide assessments to measure the level of influence and development programs to enhance the e-learning system.